Evaluation of Electronic Management in Administrative Units at the International University of Africa - Rasha Khogali Ahmed Albashair (Buletin Al-Turas, 2021)
This was study aimed at evaluating and activating the role of electronic management in the International University of Africa and knowing the fields in which electronic management was applied, and to reveal the difficulties that hindered the application of the electronic management system. A sample of the administrative staff and the statistical packages program (SPSS) were used to analyze the results, and the researcher followed the scientific management theory that aimed to reach an optimal work performance. Considering the results, the study showed that the role of electronic management in the university needed to be activated more because of the shortcomings in its activation in the management of personnel affairs, the university administration and student affairs in varying proportions that did  not achieve the required level represented in the absence of coordination between its units and the lack of knowledge of workers in this technology and it was applied in all areas of the university, and the existence of difficulties impeding the mechanism of its application. The expectations of this study lie in that it will practically contribute to the development of administrative units in Sudanese universities.